New insights on pulsating white dwarfs from 3D radiation-hydrodynamical simulations. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Tremblay, Pier-Emmanuel; Fontaine, Gilles; Ludwig, Hans-Günter; Gianninas, Alexandros; Kilic, Mukremin
Abstract: We have recently computed a grid of 3D radiation-hydrodynamical simulations for the atmosphere of pure-hydrogen DA white dwarfs in the range 5.0 < log g < 9.0. Our grid covers the full ZZ Ceti instability strip where pulsating DA white dwarfs are located. We have significantly improved the theoretical framework to study these objects by removing the free parameters of 1D convection, which were previously a major modeling hurdle. We present improved atmospheric parameter determinations based on spectroscopic fits with 3D model spectra, allowing for an updated definition of the empirical edges of the ZZ Ceti instability strip. Our 3D simulations also precisely predict the depth of the convection zones, narrowing down the internal layers where pulsation are being driven. We hope that these 3D effects will be included in asteroseismic models in the future to predict the region of the HR diagram where white dwarfs are expected to pulsate.